1999
DOI: 10.1300/j079v26n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Practices and Perceptions of School Safety

Abstract: This study of a sample of 4,044 eighth grade students taken from the National Educational Longitudinal Study of 1988 (NELS:88) was designed to examine the contribution that zero-tolerance disciplinary policies, school climate, parents' and teachers' perceptions of disciplinary climate make to students' perceptions of the school's disciplinary climate. Additionally, this study examined whether school location (i.e., urban and suburban) and school type (i.e., public and private) are associated with differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previous studies have found that students respond positively toward school violence policies that employ a broad range of rewards and sanctions for students and are based on flexibility and responsiveness to student behavior (Gottfredson et al., 2002). Flexible responses were found to be more effective in dealing with school violence, compared to strict responses that employ immediate and severe punishments and can increase the overall level of violence in the school (Farmer, 1999).…”
Section: Teacher Responses To Violence At Schoolmentioning
confidence: 99%
“…Previous studies have found that students respond positively toward school violence policies that employ a broad range of rewards and sanctions for students and are based on flexibility and responsiveness to student behavior (Gottfredson et al., 2002). Flexible responses were found to be more effective in dealing with school violence, compared to strict responses that employ immediate and severe punishments and can increase the overall level of violence in the school (Farmer, 1999).…”
Section: Teacher Responses To Violence At Schoolmentioning
confidence: 99%
“…The reason is that these problems are very common (Farmer, 1999;Kiptala, Okero & Kipturo, 2011) and that the learning setting gets disturbed through undisciplined students (Arwood, Morrow, Lane & Jolivette, 2005;Moreno, Cervelló, & Martínez Galindo, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, discipline is usually perceived as control since traditional disciplinary applications are usually based on punishment and teachers focus on being a dominant character holding the power (Boyaci, 2009;Scarlet, 1997). The related literature shows that teachers mostly tend to warn threat and punish students when they do not behave as expected or when disturbing the teaching process (Farmer, 1999;Karahanci, 2013;Kazu, 2007;Konti, 2011;Sadik, 2008;Sadik & Arslan, 2015;Sahin & Altunay, 2011;Ugurlu, Dogan, Sofortakimci, Ay &Zorlu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bullying, forcing, punishing, controlling, applying strict rules and limitations are behaviors preventing the individuals' internal discipline (Ayas & Pişkin, 2008;Başaran, 2000;Cotton, 2004;Geiger, 2000;Kabaklı Çimen & Karaboğa, 2015;Rosen, 2005;Stephens, Kyriacou & Tonnessen, 2005;Sheets,2002;Temel, 2005). However, research shows that an implementation of discipline based on bullying and forcing occurs extensively at schools (Ayas & Pişkin, 2011;Cheraghi &Pişkin, 2011;Çetin, 2013;Gökyer & Doğan, 2016;Farmer, 1999;Kabaklı Çimen & Karaboğa, 2015;Kiptala, Okero & Kipruto, 2011;Kochenderfer-Ladd &Skinner, 2002). So, the result demonstrates that discipline is provided like this at the school where the study has been performed.…”
Section: Discussionmentioning
confidence: 98%